2014
DOI: 10.1002/rcs.1572
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous antegrade scaphoid screw placement: a feasibility and accuracy analysis of a novel electromagnetic navigation technique versus a standard fluoroscopic method

Abstract: Compared with the standard fluoroscopic technique, the ENS method used in this study showed higher accuracy, less complications, required less operation and radiation exposure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Regarding nancial resources in trauma care, introducing a new navigation system is always associated with acquisition costs. Bene ts for all stakeholders have to be clear and visible [32]. However, length of surgery is an expense factor and a signi cant reduction leads to an increased cost-effectiveness overall as well as to lower infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding nancial resources in trauma care, introducing a new navigation system is always associated with acquisition costs. Bene ts for all stakeholders have to be clear and visible [32]. However, length of surgery is an expense factor and a signi cant reduction leads to an increased cost-effectiveness overall as well as to lower infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical and experimental studies have shown that electromagnetic navigation represents a reliable technique for interventional procedures like radiofrequency ablations of tumors, liver biopsies or punctures of the lumbar facet joints [ 19 , 21 23 ] [ 24 ]. However, different factors avoided the widespread use of this technique in trauma surgery [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ricci et al found in his experimental setup comparable results regarding the accuracy of electromagnetic and optical navigated guidewires [ 14 ]. Hoffmann et al postulates that the use of electromagnetic guidance in scaphoid fractures is superior to the standard fluoroscopic technique [ 24 ]. Other studies confirm these results and show a high accuracy of EM-tracking particularly during long distance interventional setups [ 13 , 15 , 16 , 18 , 19 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several surgical teams have recently sought to develop new techniques to improve guide wire positioning, such as two-dimensional (2-D) navigation (Liverneaux et al., 2008), three-dimensional (3-D) navigation (Catala-Lehnen et al., 2011), or electromagnetic navigation (Hoffmann et al., 2015). These techniques have proven to be reliable and to result in proper screw placement.…”
Section: Introductionmentioning
confidence: 99%